The Charisma of Online Group-Buying: The Moderating Role of Social Motivation - Yi-Mu Chen; Tseng-Lung Huang; Sean Hung (International Journal of Informatics and Information Systems, 2019)
Group buying can spread worldwide because the growth of the online shopping market has been considerable. In addition to deal popularity and discount rate, social motivation was included in this study. If a consumer cannot achieve an economic exchange benefit, a social exchange benefit might provide another function for the group member to stay in the community. This study adopted convenience sampling and an online questionnaire to conduct a survey. Among 240 questionnaires collected, 204 were valid. According to ANOVA analysis, the results demonstrated that social motivation has a positive influence on the relationship between the discount of a product and customers 'purchasing intention but not on the relationship between the popularity of a product and customers' purchasing intention. Therefore, we concluded that strengthening social networking can have a positive effect on customers' purchasing intention and thus encouraging the development of group purchasing retailers and related industries.